Die Erzählung von Meleagros zur literarischen Entwicklung der kalydonischen Kultlegende - Grossardt, Peter, 1963- (Mnemosyne, Supplements, 2001)
The myth of the Calydonian boar-hunt belongs to the great mythical cycles of the ancient world. P. Grossardt now offers the first complete presentation of all literary sources of the Calydonian hunt, as well as of other adventures of its central hero Meleagros. The sources have been arranged by genre and their literary context has been taken well into account. The author gives special attention to the development of different versions of the legend. Individual poets, Grossardt observes, used the myth of the Calydonian boar-hunt as a functional element in a larger context or in conscious contrast to older texts. In reconstructing the prehistory of the legend and its religious background, the author shows that the Calydonian boar-hunt myth originally had the function of an aition for the cult of Artemis Laphria and that it was taken up by the epic tradition long before Homer.